Viabilidade do uso de características “dias para um peso específico” em programas de melhoramento genético de bovinos da raça Nelore - Santana, Bruna Folegatti [UNESP] (2017)
The objective of this work was to study days for a specific weight traits in Nelore breeding programs comparing them with traditional traits such as average daily weight gain. Thus, this study aimed to estimate genetic parameters for days to reach 180kg (D180), days to reach 300kg (D300), pre-weaning weight gain (gpmdND), weight gain in the weaning period until yearling weight (gpmdDS) traits for a population of Nellore cattle. The used database consists in 60005 animals, and pedigree file information of 37234 growth phenotypes. The data were organized and prepared with the R program, and the estimation of (co) variance components, bi-character analyzes were performed with software Wombat. The progeny of the animals were analyzed for variability of progeny differences (Deps) by an additive genetic variation coefficient. The heritabilities for gpmdND and D180 were the highest, 0.4 and 0.45, respectively. The analysis demonstrated high genetic correlations between the traits gpmdND and D180 (0.99) and gpmdDS and D300 (0.95). D180 and gpmdDS showed the lowest coefficients of variation. Selection by the pre-weaning traits will produce animals that will take, on average, the same time to reach the weaning weight. However, for the D300 weight, the average gain was 82.44 days in relation to gpmdDS. Thus, a selection index that includes the traits D180 and D300 should produce the best results regarding the uniformity of the selected ones and the speed of gain.